Nutritional diagnosis of nitrogen and phosphorus in Ocimum basilicum L. plants grown under macronutrient applications - Lima, Janderson Carmo; Nascimento, Marilza Neves do; Oliveira, Uasley Caldas de; Santos, Anacleto Ranulfo dos; Brito, Gildeon Santos; Santos, Joeferson da Silva (Comunicata Scientiae, 2023)
The objective of this work was to assess the nutritional status of basil (Ocimum basilicum L.) plants grown under application of macronutrients, in a Typic Hapludult. The experiment was conducted in Cruz das Almas, BA, Brazil, in a greenhouse. The treatments were based on a Baconian matrix statistical arrangement, in which one of the nutrients is supplied in different quantities, whereas the other nutrients are maintained at the reference rates. Six nutrients, nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg) and sulfur (S) were evaluated at three different rates. Two additional treatments were used (reference rates; and without nutrient applications), totaling 20 treatments. A completely randomized experimental design with five replications was used, totaling 100 experimental units. Plant material was collected 50 days after treatment applications and dried in an oven for 72 hours. Approximately 0.1 g of dry weight of leaves, stems, and roots were subjected to acid digestion in a mixture of concentrated sulfuric acid and hydrogen peroxide. The digested material was diluted in 100 mL of distilled water to obtain the extract for nutritional diagnosis. The optimal maximum N and P accumulations in basil leaves for high plant performances were 51 and 3.0 g kg-1, respectively. The estimated rates for each nutrient to provide the optimal total N accumulation in basil plants were: N = 235.61, P =91.27, K = 175, S = 41.98 (mg dm-3), Ca = 0.97, and Mg = 0.36 (cmolc dm-3).